LEGAL PROTECTION OF THE DEBTOR CONSTRUCTION COMPLETION OF NONPERFORMING LOANS BY AUCTION OF LIABILITY WARRANTIES - Lusia Sulastri (UNISSULA, 2018)
The resolutions of non-performing loans with tendering guarantee Encumbrance Often bring up the resistance of the debtor in the form of Civil Lawsuit filed to the District Court the which is due to the complexity of the auction and Several weaknesses inherent in the Mortgage Law. Issues that will be Examined is the debtor regarding the cause of the resistance and constructing legal protection for the debtor, the which will then be Analyzed by Juridical reasons debtor resistance and constructing legal protection for debtors. Resistance debtor raises the conception of the construction of legal protection to the debtor will be maintained, as well as the Law on Consumer Protection the which regulates legal protection for debtors and Also Provides protection against collateral in the debtor from the arbitrariness of the determination of the limit value by